Stathmin1 regulates p27 expression, proliferation and drug resistance, resulting in poor clinical prognosis in cholangiocarcinoma. Issue 6 (27th May 2014) - Watanabe, Akira; Suzuki, Hideki; Yokobori, Takehiko; Tsukagoshi, Mariko; Altan, Bolag; Kubo, Norio; Suzuki, Shigemasa; Araki, Kenichiro; Wada, Satoshi; Kashiwabara, Kenji; Hosouchi, Yasuo; Kuwano, Hiroyuki
<x xml:space="preserve">Abstract</x> Patients with extrahepatic cholangiocarcinoma (EHCC) have a poor prognosis; postoperative survival depends on cancer progression and therapeutic resistance. The mechanism of EHCC progression needs to be clarified to identify ways to improve disease prognosis. Stathmin1 (STMN1) is a major cytosolic phosphoprotein that regulates microtubule dynamics and is associated with malignant phenotypes and chemoresistance in various cancers. Recently, STMN1 was reported to interact with p27, an inhibitor of cyclin‐dependent kinase complexes. Eighty EHCC cases were studied using immunohistochemistry and clinical pathology to determine the correlation between STMN1 and p27 expression; RNA interference to analyze the function of STMN1 in an EHCC cell line was also used. Cytoplasmic STMN1 expression correlated with venous invasion (P = 0.0021) and nuclear p27 underexpression (P = 0.0011). Patients in the high‐STMN1‐expression group were associated with shorter recurrence‐free survival and overall survival than those in the low‐expression group. An in vitro protein‐binding assay revealed that cytoplasmic STMN1 bound to p27 in the cytoplasm, but not in the nucleus of EHCC cells. Moreover, p27 accumulated in EHCC cells after STMN1 suppression. STMN1 knockdown inhibited proliferation and increased the sensitivity of EHCC cells to paclitaxel. STMN1 contributes to a poor prognosis and cancer progression in EHCC patients. Understanding the regulation of p27 by STMN1 could provide new insights for overcoming therapeutic resistance in EHCC.